Ruthenium Oxide, a Suitable Redox Catalyst to Mediate Oxygen Production from Water - J. Kiwi; M. Grätzel (CHIMIA)
RuO2 dispersions were found to catalyze in aqueous solution the one electron reduction of Ce4+ and Ru(bipy)33+ ions under simultaneous evolution of oxygen from water. The reaction is first order with respect to the concentration of oxidants and in the case of Ce4+ the specific rate is 0.3 h-1 at ambient temperature and 2 h-1 at 50 °C. The rate is drastically augmented when colloidal Ru dispersions are employed.